UNDERSTANDING THE EQUALITY OF HEIRS IN TAFSIR AL-MAR'ᾹH BAYN Al-ṬUGYᾹN AL-NIḌᾹM BY MUḤAMMAD SA’ĪD RAMĀḌAN AL-BŪṬI; Analysis Of QS. 4 :11 - Tajuddin, Tabrani; Awwaliyyah, Neny Muthiatul (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
This article aims to examine the thoughts of Muḥammad Sa'īd Ramāḍan al-Būṭi in his book Tafsir Al-Mar'āh Bayn al-Ṭugyān al-Niḍām. The focus of this study is emphasized on how al-Būṭi interprets the verses about the division of inheritance between men and women which have been the subject of debate among experts. By using qualitative methods and content analysis, it can be concluded that in resolving the distribution of inheritance between sons and daughters, al-Būṭi offers the concept of al-tasāwī (equality) in the distribution of inheritance between men and women, so that there is no marginalization and subordination. addressed to one party, in this case women. With this concept, it is expected that men and women can inherit a balanced inheritance. According to him, the superiority or superiority of men (ar-rijàl) over women (an-nisa') is not based on natural advantages or factors of creation, but is based on the quality of management, wisdom and the level of culture and awareness that differs among humans. According to him, Islamic inheritance law is not measured by the level of equality between heirs, but is determined based on the size of the burden or responsibility that is developed for them, in terms of the general condition of their lives.